Soil Reinforcement using Waterglass and Sulfuric Acid with Injection Grouting Method - Irwan, .; Djamaluddin, Abdul Rachman; Muhiddin, Achmad Bakri; Arsyad, Ardy (Engineering, Technology & Applied Science Research, 2025)
A common problem often encountered in infrastructure development, especially in tunnelling projects, involves non-cohesive soils with high groundwater levels. In tunnelling projects, the existence of non-cohesive soil is very susceptible to collapse, hindering work and even causing loss of life and damage to buildings around the construction area. To prevent such a non-cohesive soil collapse, a barrier or temporary wall is needed for the jacking installation to be carried out safely. An efficient method to achieve this is temporary reinforcement with the injection grouting method using waterglass and sulfuric acid as activators. Waterglass and sodium silicate are widely utilized in construction. This study deploys an experimental approach with two testing concepts to obtain the composition of grout materials. The first test involves simulating tunnelling on unsaturated sandy soil, while the second test is carried out on saturated sandy soil to simulate high groundwater level conditions. The analysis was conducted based on the characteristics of the sandy soil collapse zone, using parameters, such as the coefficient of permeability, direct shear test results, soil density, and index properties. The test was carried out using grouting injection with waterglass and sulfuric acid, which proved effective, since they formed a gel layer that prevents the collapse of non-cohesive soil, even under high groundwater level conditions. The novelty of this study lies in the combination of waterglass and sulfuric acid with an optimal composition with the change to gel faster to improve time efficiency during construction.